2019
DOI: 10.1038/s41574-019-0242-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the glucoregulatory mechanisms of metformin in type 2 diabetes mellitus

Abstract: Despite its position as the first-line treatment for type 2 diabetes mellitus, the mechanisms underlying the plasma glucose level-lowering effects of metformin (1,1dimethylbiguanide) still remain incompletely understood. Metformin is thought to exert its primary antidiabetic action through the suppression of hepatic glucose production. Furthermore, the discovery that metformin inhibits the mitochondrial respiratory-chain complex 1 has placed energy metabolism and activation of AMP-activated protein kinase (AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
360
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 475 publications
(416 citation statements)
references
References 254 publications
5
360
0
1
Order By: Relevance
“…Therefore, we measured IGF-1 signaling in metformin-treated liver and skeletal muscle samples using western blotting. We found that the expression/activation of IGF-1R was increased in the liver of metformin-treated iMSUD mice, which is consistent with previous reports ( Figure S2A) (25). The expression/activation of IGF-1R was diminished in the skeletal muscle of iMSUD mice, and metformin mitigated this effect ( Figure S2A).…”
Section: Metformin-induced Decreased Glucose Intolerance In Imsud Micesupporting
confidence: 92%
“…Therefore, we measured IGF-1 signaling in metformin-treated liver and skeletal muscle samples using western blotting. We found that the expression/activation of IGF-1R was increased in the liver of metformin-treated iMSUD mice, which is consistent with previous reports ( Figure S2A) (25). The expression/activation of IGF-1R was diminished in the skeletal muscle of iMSUD mice, and metformin mitigated this effect ( Figure S2A).…”
Section: Metformin-induced Decreased Glucose Intolerance In Imsud Micesupporting
confidence: 92%
“…Forced overexpression of NMT1 brings AMPK to the lysosomal membrane, avoids mTORC1 activation, and suppresses tissue inflammation . The anti‐diabetic drug metformin functions as an AMPK activator . However, treating RA T cells with metformin failed to restore AMPK activation and left mTORC1 activation unaffected.…”
Section: Ra T Cells Misplace Amp‐activated Protein Kinase (Ampk) To Nmentioning
confidence: 99%
“…75 The anti-diabetic drug metformin functions as an AMPK activator. 83 However, treating RA T cells with metformin failed to restore AMPK activation and left mTORC1 activation unaffected. A769662 is a small molecule that activates extra-lysosomal AMPK.…”
Section: R a T Cell S Mis Pl Ace Amp -Ac Tivated Protein K Ina S E mentioning
confidence: 99%
“…Metformin binds a series of different transitional metals, having a higher affinity for copper [89]. In particular, the interaction of metformin with mitochondrial copper, resulting in the alteration of cellular energy metabolism via inhibition of mitochondrial respiratory chain complex 1, has been proposed as a putative mechanism of action of the drug [90]. Treatment with TM has been described to promote a significant reduction of insulin resistance in the mouse model of type II diabetes C57BL/KsJ-db/db [91].…”
Section: Diabetes Mellitusmentioning
confidence: 99%